Enhancing Business Performance: A Dual Perspective of Customer Experience Mediation and Technological Readiness Moderation - Putra, Bagusranu Wahyudi; Sembiring, Murpin Josua; Dewi, Liliana; Ardissalma, Jasmine (Jurnal Aplikasi Manajemen, 2025)
This study investigates the intricate dynamics of digital transformation programs and business performance, with an emphasis on the mediating role of customer experience optimization and the moderating role of technology infrastructure preparedness. Based on survey responses from 247 executives across various industries in Indonesia, this study uses structural equation modeling to estimate the posited relationships. The results verify that digital transformation positively influences business performance, both directly and indirectly, through better customer experience. Additionally, preparedness of technology infrastructure strongly moderates the alignment of digital transformation with customer experience optimization, such that firms well prepared in this regard derive the maximum benefits from their digital programs. The current work contributes to existing foundational theories by identifying key mediating and moderating mechanisms that explain heterogeneity in digital transformation returns, dispelling naive deterministic conceptions of technological dynamics. The results provide actionable insights for business executives who want to maximize returns on their digital investments. They emphasize strategic alignment across digital transformation, customer experience optimization, and technology infrastructure preparedness as the cornerstones of effective digital programs. The current work contributes to the body of knowledge in digital business strategy by clarifying the intricate mechanisms by which digital investments translate into superior business performance.